GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Drought projections for the NW Iberian Peninsula under climate change - I. Alvarez; H. Pereira; M. N. Lorenzo; A. Picado; M. C. Sousa; J. J. Taboada; J. M. Dias (Climate Dynamics, 2024)
Drought can be considered an atmospheric condition, which rapidly goes beyond to affect multiple fields of the environment and human activities. The persistence of these atmospheric conditions can affect the recharge of surface and groundwater bodies due to a decrease in the volume of runoff and seepage, thus affecting human and environmental activities. In this context, the main aim of this work is to characterize the occurrence and variability of future droughts in Galicia over the twenty-first century. The methodology followed is based on the calculation and analysis of the Standardized Precipitation Index (SPI) in three-time scales (3, 6, and 12 months), using daily outputs of precipitation data from one RCM provided by the EURO-CORDEX project for different periods (reference from 1971 to 2005, and future from 2025 to 2060 and 2061 to 2096) and scenarios (RCP 4.5 and RCP 8.5). Using SPI-3, SPI-6, and SPI-12 projections, drought trends and potential changes in their characteristics were explored under RCP 4.5 and RCP 8.5 scenarios. In both scenarios, throughout the twenty-first century, a decreasing trend in SPI indicates an intensification of drought conditions over Galicia. Moreover, at the beginning of the century, under RCP 4.5, drought events will increase and will be slightly more intense but less persistent, while under RCP 8.5, the number of events will be almost the same, but shorter and less severe. Toward the end of the century, drought events are expected to be more numerous, less durable, and more intense under both scenarios.

Corrigendum to “Priorities to inform research on marine plastic pollution in Southeast Asia” [Sci. Total Environ. volume 841 (2022) Article 156704] - Lucy C.M. Omeyer; Emily M. Duncan; Kornrawee Aiemsomboon; Nicola Beaumont; Sujaree Bureekul; Bin Cao; Luis R. Carrasco; Suchana Chavanich; James R. Clark; Muhammad R. Cordova; Fay Couceiro; Simon M. Cragg; et al. (Science of The Total Environment, 2023)

Variability of photosynthetic and related traits in maize and other summer crops in a temperate humid area - Lorena Álvarez-Iglesias; María I. Vales; Antonio M. De Ron; Ana P. Rodiño; Juan L. Tejada-Hinojoza; Alfredo Taboada; Pedro Revilla (Plant Physiology Reports, 2022)
Photosynthetic rate and water use efficiency (WUE) are crucial for the sustainable use of water in agriculture. Our objective was to analyze the variability of photosynthetic and related traits in maize ( Zea mays L.) and other summer crops in a temperate humid area. We evaluated photosynthetic parameters in maize for three years and compared them to pigeonpea and chickpea, adapted to arid environments, and pepper, tomato and common bean, as irrigated crops. Variability was significant in maize for most photosynthetic parameters and no consistent patterns of variability were found among genotypes. Compared to other crops, maize (C 4 crop) had the highest CO 2 assimilation and WUE, and the lowest stomatal conductance, substomatal CO 2 concentration, and transpiration. CO 2 assimilation was lowest for chickpea, stomatal conductance was highest for pigeonpea, substomatal CO 2 concentration was highest for tomato and pigeonpea, transpiration was highest for pigeonpea, and WUE was lowest for pigeonpea. Chickpea lacked variability for photosynthetic traits, while pigeonpea has the largest potential for improving photosynthetic traits. Net assimilation, conductance, and transpiration could be improved in common bean, and substomatal CO 2 concentration in pepper. Water Use Efficiency could be improved in some C 3 crops, but more genetic biodiversity has to be identified in maize.

Resonance Raman imaging as a tool to assess the atmospheric pollution level: carotenoids in Lecanoraceae lichens as bioindicators - I. Ibarrondo; N. Prieto-Taboada; I. Martínez-Arkarazo; J. M. Madariaga (Environmental Science and Pollution Research, 2016)

Analysis and detection of functional outliers in water quality parameters from different automated monitoring stations in the Nalón River Basin (Northern Spain) - J. I. Piñeiro Di Blasi; J. Martínez Torres; P. J. García Nieto; J. R. Alonso Fernández; C. Díaz Muñiz; J. Taboada (Environmental Science and Pollution Research, 2015)

The problem of sampling on built heritage: a preliminary study of a new non-invasive method - N. Prieto-Taboada; C. Isca; I. Martínez-Arkarazo; A. Casoli; M. A. Olazabal; G. Arana; J. M. Madariaga (Environmental Science and Pollution Research, 2014)

Turbidity Prediction in a River Basin by Using Artificial Neural Networks: A Case Study in Northern Spain - C. Iglesias; J. Martínez Torres; P. J. García Nieto; J. R. Alonso Fernández; C. Díaz Muñiz; J. I. Piñeiro; J. Taboada (Water Resources Management, 2014)

Nutritional value of the marine algae wakame (Undaria pinnatifida) and nori (Porphyra purpurea) as food supplements - M. C. Taboada; R. Millán; M. I. Miguez (Journal of Applied Phycology, 2013)

Triterpene glycosides from Antarctic sea cucumbers III. Structures of liouvillosides A 4 and A 5 , two minor disulphated tetraosides containing 3- O -methylquinovose as terminal monosaccharide units from the sea cucumber Staurocucumis liouvillei (Vaney) - Alexandr S. Antonov; Sergey A. Avilov; Anatoly I. Kalinovsky; Pavel S. Dmitrenok; Vladimir I. Kalinin; Sergi Taboada; Manuel Ballesteros; Conxita Avila (Natural Product Research, 2011)

Predictability of the spring rainfall in Northwestern Iberian Peninsula from sea surfaces temperature of ENSO areas - M. Nieves Lorenzo; J. J. Taboada; I. Iglesias; M. Gómez-Gesteira (Climatic Change, 2011)

Relationship between monthly rainfall in northwest Iberian Peninsula and North Atlantic sea surface temperature - M. N. Lorenzo; I. Iglesias; J. J. Taboada; M. Gómez‐Gesteira (International Journal of Climatology, 2010)
This study assesses the relationship between monthly North Atlantic sea surface temperature anomalies (SSTAs) and a regional index of rainfall (NWIPR) in northwest Iberian Peninsula during the period 1951–2006 by means of the Pearson product‐moment correlation. Results show a strong influence of SSTA on NWIPR in several months (February, April, May, October and December). The observed persistence of this influence up to 2‐months in advance can be used for monthly predictions of rainfall. The most significant areas of the North Atlantic were clustered to be used as input variables in linear regression models. Correlations up to 0.59 between observed and predicted rainfall anomalies were obtained. Predictability ranged from 76 to 86% when considering rainfall as a discrete predictand. Copyright © 2009 Royal Meteorological Society